Gambaran Program Imunisasi Pada Balita Zero Dose Di Kota Binjai Tahun 2025 - Wahyudi, Wahyudi; Almarendi, Alvi Azmi; Amanda, Bella; Warina, Yunita; Aryulika, Mawar; Atifah, Nur; Utami, Dilla Fitri (Yayasan Jompa Research and Development, 2025)
Immunization is one of the most important public health programs to prevent infectious diseases and reduce child mortality. Children with zero doses reflect disparities in access to primary healthcare services. In Binjai City, despite the implementation of data collection and follow-up vaccination programs, several toddlers have still not received vaccines according to the recommended schedule. This study aims to describe the implementation of vaccination among zero-dose toddlers in Binjai City in 2025. This research used a descriptive design with a cross sectional approach based on secondary data from the Binjai City Health Office involving 57 zero dose toddlers. The variables analyzed included the mother’s age, child’s age, mother’s educations grade, mother’s occupation, child’s gender, and types of vaccines provided. Data were analyzed descriptively by frequency distribution and percentages. The results showed that the mean age of mothers was 29.35 years, and the average age of children was 11.33 months. Most mothers wre junior high school education (59.6%) and were housewives (47.4%), while the proportion of female children was slightly higher than males (52.6% vs. 47.4%). The most frequently provided vaccines were DPT1, BCG, and Polio (54%). In conclusion, the implementation of immunization among zero-dose toddlers in Binjai City remains suboptimal, particularly in follow-up and target tracking.